Faktor-faktor yang Mempengaruhi Kepuasan Pengguna Mobile Banking: Studi Empiris pada Nasabah BCA di Sumatera Barat - Stefanie Renata Maharani; Asniati Bahari (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The purpose of this study is to present empirical data regarding the impact of system quality, information quality, service quality, and system security on user satisfaction among West Sumatera BCA mobile banking customers. Data for this study were obtained through an online survey completed by 235 participants. The analysis indicates that both system quality and information quality significantly and positively influence user satisfaction. Conversely, service quality and system security do not demonstrate a notable effect. These insights are valuable for service providers, emphasizing the importance of enhancing system functionality, ensuring the accuracy of information, improving service delivery, and strengthening system security to better align with user expectations. Additionally, mobile banking users are encouraged to take these four elements into account when choosing a digital banking platform to ensure a more efficient and satisfying experience.